2013
DOI: 10.3109/10582452.2013.852150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Using a Progressive Muscle Relaxation Technique in Reducing the Pain of Multiple Sclerosis Patients

Abstract: Objective: Multiple sclerosis is a chronic neurological disease that affects all financial, social and emotional aspects of individuals, families, and society in general. The pain caused by this disease can have devastating effects on patients and their careers, and thus the quality of their lives. This study aimed at verifying the level of pain in multiple sclerosis [MS] patients before and after the application of a progressive muscle relaxation technique [PMRT]. Methods: In a randomized clinical trial stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In line with the current study, numerous internal studies on other chronic diseases with common grounds, such as multiple sclerosis, 49 and patients with acute leukemia 50 also showed high levels of care costs for chronic patients. In the McGuire’s quality Study, caregivers of comatose patients indicated their complicated financial situations despite being sponsored by insurance companies or the state.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the current study, numerous internal studies on other chronic diseases with common grounds, such as multiple sclerosis, 49 and patients with acute leukemia 50 also showed high levels of care costs for chronic patients. In the McGuire’s quality Study, caregivers of comatose patients indicated their complicated financial situations despite being sponsored by insurance companies or the state.…”
Section: Discussionsupporting
confidence: 89%
“…: guided imagery, controlled breathing, progressive muscle relaxation, etc.) (Masoudi et al 2013;Topcu and Findik 2012;Chen and Francis 2010;Lebovits 2007); stress management (Marchand 2012); biofeedback (Mora et al 2013); coping skills training (Alschuler et al 2013;Emery et al 2006); and, hypnosis (Adachi et al 2014).…”
Section: Treatment Of Pain and Insomniamentioning
confidence: 99%
“…The trials included in the review were published between 2003 and 2021. Among the included trials, cNeP was secondary to SCI ( n = 8), 38 45 multiple sclerosis ( n = 7), 46 52 stroke ( n = 4), 53 – 56 or phantom limb pain ( n = 4). 57 60 The interventions evaluated by the included trials for the treatment of pain were TENS ( n = 4), 46 49 rTMS ( n = 6), 38 , 41 , 43 , 53 , 54 , 59 transcranial direct current stimulation (tDCS, n = 5), 39 , 40 , 44 , 45 , 60 mirror therapy ( n = 2), 57 , 58 exercise ( n = 3), 50 52 acupuncture ( n = 2), 55 , 56 and spinal cord stimulation ( n = 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%